1996
DOI: 10.2466/pms.1996.83.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance is Not a Viable Determinant of Physical Therapy Students' Burnout

Abstract: This study investigated the proposed link between students' academic performance and burnout. We found no significant correlations between students' cumulative grade point average and ratings of emotional exhaustion, depersonalization, and personal accomplishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 2 publications
1
50
0
7
Order By: Relevance
“…In previous adaptations of the original MBI, instructors was substituted for recipients (e.g., Balogun et al, 1996;Gold & Michael, 1985), which is problematic because it might change the meaning of the particular items involved. However, because the MBI-GS is a more generic instrument that measures burnout without referring to other people, such inherent problems of rewording are avoided.…”
mentioning
confidence: 99%
“…In previous adaptations of the original MBI, instructors was substituted for recipients (e.g., Balogun et al, 1996;Gold & Michael, 1985), which is problematic because it might change the meaning of the particular items involved. However, because the MBI-GS is a more generic instrument that measures burnout without referring to other people, such inherent problems of rewording are avoided.…”
mentioning
confidence: 99%
“…Fora das profissões de ajuda, a exaustão emocional passou a ser designada simplesmente por exaustão, a despersonalização passou a chamar-se cinismo e a realização pessoal transformou-se em eficácia profissional. O conceito de burnout tem também sido aplicado a pessoas envolvidas em actividades que, não sendo profissões propriamente ditas, partilham com elas alguns pontos comuns, como é o caso de mães a tempo inteiro (Pelsma, Roland, Tollefson, & Wigington, 1989) e de estudantes (Balogun, Helgemoe, Pellegrini, & Hoeberlein, 1996;Koeske & Koeske,1991;McCarthy, Pretty, & Catano, 1990;Schaufeli, Martinez, Marques Pinto, Salanova, & Bakker, 2002).…”
Section: Introductionunclassified
“…Essa adaptação foi feita por Schaufeli, Martinez, Marques Pinto, Salanova, e Bakker (2002), a partir de trabalhos anteriores (Balogun et al, 1996;Gold & Michael, 1985) tendo por base o MBI-GS. Recebendo o nome de Maslach Burnout Inventory -Student Survey (MBI-SS), a escala ficou constituída por 15 itens, tendo a dimensão despersonalização/ /cinismo passado a ser designada por Descrença .…”
Section: Introductionunclassified
“…However, no studies were found in the literature that investigated the relationship between academic burnout and the classroom assessment environment. Since academic burnout brings about numerous negative characteristics such as depression (Capri & Yedigoz Sonmez, 2013), lack of motivation, increased tendency to absenteeism, dropout (Meier & Schmeck, 1985;Yang, 2004), and low academic achievement (Balkis, 2013;Balogun, Hoeberlein, Schneider & Katz, 1996), identifying the assessment practices that work in favor of, as well as those that work against, academic burnout is of great importance -both for the students' health and for the functioning of the education system (Aypay & Eryilmaz, 2011). By examining the relationship between academic burnout and the classroom assessment environment, it might be possible to determine what kind of an assessment environment should be established in order to decrease students' experience of academic burnout.…”
Section: Relationship Between Academic Burnout and The Classroom Assementioning
confidence: 99%